Performance evaluation of the current construction of the Great Wall of China in Jinshanling: using a fuzzy system. Issue 3 (2nd October 2017) - Yang, Jin; Tan, Fabian Hadipriono; Tan, Adrian; Parke, Michael
ABSTRACT: This research paper focuses on evaluating the performance of the Great Wall of China in Jinshanling using the Fuzzy Performance Tree Analysis (FPTA), Baldwin's fuzzy-set rotational model, and defuzzification using the centroid and mean methods. The inputs for the performance tree analysis and Baldwin's model are derived from the knowledge base of the authors' earlier study. The outputs from the defuzzification process show that the Jinshanling section of the Great Wall is fairly severe in terms of damages, and immediate repair should be performed to prevent additional damages, especially in the eastern and western Jinshanling sections. The results derived from this evaluation process provide consistent, quantitative, and systematic conclusions concerning the current performance of the structure. The authors hope that these scientific methodologies introduced in this paper would be further researched and implemented in evaluating the performance of other facilities, both ancient and modern.